Performance-based assessment: Self-efficacy, decision-making, and problem-solving skills in learning science - Yvette M. Villarta; Levi T. Atibula; Flordeliza S. Gagani (Journal La Edusci, 2021)
Performance-based assessment is a purposive-oriented assessment activity in revealing student understanding of unwrapped concepts, skills, and big ideas. This study aimed to determine the effects of performance task assessment on the students' self–efficacy, problem–solving, and decision–making skills in learning science that used the quantitative and correlation methods of research. There were 35 Grade 9 students of the University of San Carlos, Basic Education Department – South Campus in science class as respondents of the study. The assessment was given after the engagement session of the instructional plan to be accomplished after the transfer task session and evaluated using specific rubrics. A modified Albert Bandura's Instrument was used to measure self–efficacy and Mind Tool: Essential Skill for Excellent Career questionnaires for the problem–solving and decision–making skills of the students in learning science. The study's findings indicated that the Performance Assessment developed students' self–efficacy in learning science and had a significant impact on how students think, feel, and behave in the process of learning. Moreover, the assessment conveyed positive influence in developing students' problem–solving and decision–making skills. This assessment encouraged students to apply the scientific processes in evaluating the identified options before deciding the problem's solution.